Gender discrimination in Qur’anic interpretation: Challenges and opportunities of inclusive hermeneutics - Aidatul Fitriyah; Gohar Rahman (An-Nisa’ Journal of Gender Studies, 2024)
Gender discrimination in classical interpretations of the Qur’an persists due to patriarchal bias, while inclusive hermeneutics continues to face conservative resistance despite offering opportunities for justice through feminist reinterpretation. This study aims to analyze gender bias in Qur’anic interpretation, examine structural challenges in developing inclusive interpretations, and explore opportunities for reconstructing egalitarian gender interpretations relevant to contemporary social dynamics. The study employs gender hermeneutics through a Systematic Literature Review (SLR) method using thematic analysis of classical and contemporary interpretations to identify patriarchal bias and reconstruct gender-inclusive Qur’anic interpretations. The findings reveal three main points: 1) gender bias in the interpretation of QS. 4:34, 4:11, and 4:3 originates from classical patriarchy. Contextual hermeneutics reconstructs the concept of qawwam toward a more inclusive and equitable interpretation of the Qur’an. 2) Inclusive interpretation is hindered by conservative resistance, male-dominated religious institutions, patriarchal legitimization of sharia, and limited female participation in contemporary interpretive reform. 3) Opportunities for reconstructing gender interpretations are supported by global awareness, education, digital technology, changing women’s roles, and international collaboration toward contextual interpretation. The study concludes that gender bias in Qur’anic interpretation is rooted in classical patriarchal structures. Although contextual reconstruction faces structural barriers, education, technology, global awareness, and international collaboration provide opportunities for more equitable interpretations. This study contributes to strengthening contextual hermeneutics, encouraging gender reinterpretation, advocating for equitable family law, utilizing digital media, and increasing women’s participation in religious authority and Qur’anic interpretation.